2009
DOI: 10.3354/meps08156
|View full text |Cite
|
Sign up to set email alerts
|

Vertical dynamics and reproductive behaviour of farmed and wild Atlantic cod Gadus morhua

Abstract: Rapid development of fish mariculture and efforts to restock depleted populations have raised concerns about the effects on wild populations and the risk of genetic introgression from hybridisation. Reproduction of many marine fish species involves substantial vertical movements, but nothing is known of the vertical dynamics of farmed fish in spawning shoals. We combined laboratory observations and field biotelemetry to examine the depth-related reproductive behaviour and vertical dynamics of individual farmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
2
29
0
2
Order By: Relevance
“…Recently fertilised cod eggs were found in all 12 samples. Further information about the wild and farmed fish can be found in Meager et al (2009Meager et al ( , 2010.…”
Section: Study Site and Experimental Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently fertilised cod eggs were found in all 12 samples. Further information about the wild and farmed fish can be found in Meager et al (2009Meager et al ( , 2010.…”
Section: Study Site and Experimental Fishmentioning
confidence: 99%
“…The inter-batch interval of cod females is highly affected by ambient temperature (Kjesbu 1989), and females are likely to seek out a depth that optimises the developmental time of oocytes. The spawning event itself, where a male and female engage in a mating embrace (Brawn 1961, Skjaeraasen & Hutchings 2010, is associated with upwards vertical movement (Meager et al 2009). Finally, although cod appetite during spawning is believed to be reduced (Fordham & Trippel 1999, Skjaeraasen et al 2004, cod do feed at this time (Michalsen et al 2008), and fish may thus undertake foraging excursions towards the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for negative ecological consequences is significant (Bekkevold et al 2006). For example, research has shown that escaped farmed cod are present on spawning areas for wild cod during the spawning season and that wild and escaped cod are likely to interbreed (Uglem et al 2008, Meager et al 2009). Within sea cages, farmed cod are also capable of producing viable cod larvae which subsequently mix with larvae from wild cod in the areas around cod farms (Jørstad et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that escaped farmed cod are present in spawning areas for wild cod during the spawning season and that wild and escaped cod are likely to interbreed , Meager et al 2009). Farmed cod are also capable of producing viable cod larvae within sea cages, which subsequently mix with larvae from wild cod in the areas around cod farms (Jørstad et al 2008).…”
Section: Introductionmentioning
confidence: 99%